Meta-Analisis : Efektivitas Multimedia Interaktif terhadap Peningkatkan Hasil Belajar Siswa - Khaeruman Khaeruman; AAIA Rai Sudiatmika; I Ketut Suma; I Nyoman Suardana (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This research aims to determine the effectiveness of interactive multimedia on student learning outcomes by analyzing 15 articles that can be accessed from Google Scholar, Garuda, and Mendeley. These articles were published in non-accredited journals, accredited Sinta, and indexed by Copernicus or Scopus with 5 different sample levels, namely: Elementary School, Middle School, High School, Vocational High School, and College. The use of interactive multimedia contains text, graphics, audio and moving images (video) which can be displayed via projector and laptop screens. This research method uses a meta-analysis method, namely by comparing research data from control and experimental groups in the form of sample size (N), Standard Deviation (SD), and learning outcomes (X). The data was analyzed statistically to see the effect size value. Based on the results of the analysis test, it was found that from the 15 articles analyzed, the average effect size was 1.146 with a P-Value < 0.001 (P-Value < 0.05), which means that learning using multimedia is very effective or has an influence on student learning outcomes. Next, to see at which level the effectiveness value is higher, the analysis results found that the estimated value at the elementary school level was 1.719 (more effective), followed by the tertiary level with an estimate of 1.707.